Intensified chemotherapy and dose-reduced involved-field radiotherapy in patients with early unfavorable Hodgkin's lymphoma: final analysis of the German Hodgkin Study Group HD11 trial - Eich, Hans Theodor; Diehl, Volker; Görgen, Helen; Pabst, Thomas; Markova, Jana; Debus, Jürgen; Ho, Anthony Dick; Dörken, Bernd; Rank, Andreas; Grosu, Anca-Ligia; Wiegel, Thomas; Karstens, Johann Hinrich; et al. (Journal of clinical oncology, 2010)
Purpose: Combined-modality treatment consisting of four to six cycles of chemotherapy followed by involved-field radiotherapy (IFRT) is the standard of care for patients with early unfavorable Hodgkin's lymphoma (HL). It is unclear whether treatment results can be improved with more intensive chemotherapy and which radiation dose needs to be applied. - Patients and Methods: Patients age 16 to 75 years with newly diagnosed early unfavorable HL were randomly assigned in a 2 × 2 factorial design to one of the following treatment arms: four cycles of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) + 30 Gy of IFRT; four cycles of ABVD + 20 Gy of IFRT; four cycles of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPPbaseline) + 30 Gy of IFRT; or four cycles of BEACOPPbaseline + 20 Gy of IFRT. - Results: With a total of 1,395 patients included, the freedom from treatment failure (FFTF) at 5 years was 85.0%, overall survival was 94.5%, and progression-free survival was 86.0%. BEACOPPbaseline was more effective than ABVD when followed by 20 Gy of IFRT (5-year FFTF difference, 5.7%; 95% CI, 0.1% to 11.3%). However, there was no difference between BEACOPPbaseline and ABVD when followed by 30 Gy of IFRT (5-year FFTF difference, 1.6%; 95% CI, −3.6% to 6.9%). Similar results were observed for the radiotherapy question; after four cycles of BEACOPPbaseline, 20 Gy was not inferior to 30 Gy (5-year FFTF difference, −0.8%; 95% CI, −5.8% to 4.2%), whereas inferiority of 20 Gy cannot be excluded after four cycles of ABVD (5-year FFTF difference, −4.7%; 95% CI, −10.3% to 0.8%). Treatment-related toxicity occurred more often in the arms with more intensive therapy. - Conclusion: Moderate dose escalation using BEACOPPbaseline did not significantly improve outcome in early unfavorable HL. Four cycles of ABVD should be followed by 30 Gy of IFRT.